Ethics and Ego: East-West Perceptions of Morality - Geir Sigurðsson (Nordicum-Mediterraneum, 2014)
The thesis from which this comparison proceeds is that the major differences between the East-Asian and Western ethical traditions emanate from divergent views of the kind of role selfhood or ego should play in social human life. A comparison of these views, it is suggested, will be helpful to flesh out the different perceptions of morality. It will be proposed that Western thinking is characterized by a stronger focus on the self, and that while Western ethical thinkers and schools certainly seek to reduce self-centeredness, such endeavours generally proceed through an augmentation of the role of human reason and thus a more intense and even tormenting self-consciousness. A clear reflection of this tendency is the ethical approach to moral issues qua issues associated with individual action and rational choice. The East-Asian approach differs from this in that it seeks to balance excessive introspection with a cultivated ‘sense’ of identification with the whole, be it society or the natural realm. While this approach, it seems, largely succeeds in preventing an existential kind of agony, it nevertheless suffers from some other serious weaknessess. Hence both traditions, it is argued, have something to offer one other. The discussion offered here is merely a sketchy outline that may hopefully work as a first step toward that purpose.